Stacked denoising autoencoders for sentiment analysis: a review. (9th June 2017) - Sagha, Hesam; Cummins, Nicholas; Schuller, Björn
Abstract : Deep learning has been shown to outperform numerous conventional machine learning algorithms (e.g., support vector machines) in many fields, such as image processing and text analyses. This is due to its outstanding capability to model complex data distributions. However, as networks become deeper, there is an increased risk of overfitting and higher sensitivity to noise. Stacked denoising autoencoders (SDAs) provide an infrastructure to resolve these issues. In the field of sentiment recognition from textual contents, SDAs have been widely used (especially for domain adaptation), and have been consistently refined and improved through defining new alternate topologies as well as different learning algorithms. A wide selection of these approaches are reviewed and compared in this article. The results coming from the reviewed works indicate the promising capability of SDAs to perform sentiment recognition on a multitude of domains and languages. WIREs Data Mining Knowl Discov 2017, 7:e1212. doi: 10.1002/widm.1212 This article is categorized under: Algorithmic Development > Text Mining Technologies > Machine Learning Abstract : (a) Autoencoder, (b) Denoising Autoencoder, (c) SDA with Domain and Sentiment Supervision (SDA‐DSS), (d) Domain Adversarial Neural Network (DANN) with 'SDA representation'.